Chronic Hypertension Related to Risk for Preterm and Term Small-for-Gestational-Age Births - Catov, Janet M. (2008)
OBJECTIVE: Evidence relating chronic hypertension to risk of small for gestational age (SGA) births is conflicting. To identify factors associated with SGA that may involve a placental pathogenesis, we related chronic hypertension and other maternal factors that may be markers of endothelial dysfunction to preterm compared with term SGA births. METHODS: Chronic hypertension, diabetes, body mass index, age, and subfertility were related to risk of term and preterm SGA births in the Danish National Birth Cohort (n=81,008). SGA births were those with a birth weight adjusted for gestational age greater than 2 standard deviations below the mean based on fetal growth curves. RESULTS: Risk of preterm SGA increased 5.5-fold (95% CI 3.2-9.4) and risk of term SGA increased 1.5-fold (1.0-2.2) among women with definite chronic hypertension. Risk of preterm SGA but not term SGA was increased among women less than 20 (odds ratio [OR] 2.8, 95% CI: 1.1-6.8) or greater than 36 (OR 2.0 , 95% CI:1.3-3.1) years of age and among those with at least 2 early spontaneous abortions (OR 2.0, CI:1.3-3.3). Smoking, parity, time to pregnancy greater than 12 months, and underweight status were similarly related to term and preterm SGA. Overweight status, obesity, and presence of diabetes were unrelated to either SGA subtype. CONCLUSIONS: Chronic hypertension, young or older maternal age, and recurrent early spontaneous abortions increased risk for preterm SGA. These factors may involve abnormal placentation and likely represent a pathogenesis distinct from that leading to term SGA.